MGL1 promotes adipose tissue inflammation and insulin resistance by regulating 7/4(hi) monocytes in obesity - Westcott, Daniel J. (The Rockefeller University Press, 2009)
Adipose tissue macrophages (ATMs) play a critical role in obesity-induced inflammation and insulin resistance. Distinct subtypes of ATMs have been identified that differentially express macrophage galactose-type C-type lectin 1 (MGL1/CD301), a marker of alternatively activated macrophages. To evaluate if MGL1 is required for the anti-inflammatory function of resident (type 2) MGL1(+) ATMs, we examined the effects of diet-induced obesity (DIO) on inflammation and metabolism in Mgl1(−/−) mice. We found that Mgl1 is not required for the trafficking of type 2 ATMs to adipose tissue. Surprisingly, obese Mgl1(−/−) mice were protected from glucose intolerance, insulin resistance, and steatosis despite having more visceral fat. This protection was caused by a significant decrease in inflammatory (type 1) CD11c(+) ATMs in the visceral adipose tissue of Mgl1(−/−) mice. MGL1 was expressed specifically in 7/4(hi) inflammatory monocytes in the blood and obese Mgl1(−/−) mice had lower levels of 7/4(hi) monocytes. Mgl1(−/−) monocytes had decreased half-life after adoptive transfer and demonstrated decreased adhesion to adipocytes indicating a role for MGL1 in the regulation of monocyte function. This study identifies MGL1 as a novel regulator of inflammatory monocyte trafficking to adipose tissue in response to DIO.